Laramide contractional folding in the Devils River Uplift, west Texas, U.S.A. (October 2022) - Ferrill, David A.; Smart, Kevin J.; Evans, Mark A.; Cawood, Adam J.; Bellow, Harrison B.; Morris, Alan P.; McGinnis, Ronald N.
Abstract: Structures in Cretaceous strata in the Devils River Uplift of west Texas include folds, thrust faults, and bedding-parallel veins indicative of contractional deformation in a thrust faulting stress regime. In this study we analyze a series of small-wavelength (meters to tens of meters) folds in roadcut exposures northwest of Del Rio, Texas. The folds have WNW-ESE dominant trends, gently plunging axes, and are gentle to tight with upright to inclined axial surfaces of variable vergence. These structures are interpreted as detachment folds, with detachments within volcanic ash or mudrock beds. Observed thickening in anticline cores was by ductile flow of volcanic ash or mudrock, small-scale folding, and thrust or reverse faulting. Bed-perpendicular calcite veins are common and in some cases are offset by flexural slip on fold limbs, indicating that folding occurred after brittle failure and extension vein formation in lithified rock. Although rare, bed-parallel calcite veins are also present in the exposure and indicative of a thrust faulting stress regime. Occasional normal and reverse or thrust faults are also present in the exposures. Fluid inclusion analysis of vein cements from extension fractures and faults yielded homogenization temperatures of 71–101 °C, and estimated trapping depths of 2.2–3.5 km prior to and coeval with folding. We interpret these folds as having formed during NNE-SSW directed Laramide shortening (∼80–40 Ma) in a thrust-faulting stress regime with >2 km of overburden, rather than as either penecontemporaneous with deposition or after exhumation by caliche formation, as previously interpreted. Highlights: Analyses of small-wavelength folds in Devils River Uplift, west Texas. Folds are typically detached above volcanic ash or mudrock beds. Calcite veins offset by flexural-slip on fold limbs – bed-parallel veins rare. Vein fluid inclusions trapped at 71–101 °C, and depths of 2.2–3.5 km. Folds record NNE-SSW directed Laramide shortening.